Simulating protein folding with full atomistic detail - Pande, Vijay (Henry Stewart Talks, 2007)
Protein folding and disease, Folding kinetics can have a biological impact, Why use physical simulation?, Primary challenges, Possible models, Building atomistic models, Modern force fields, Ways to treat water, Implicit solvent models, Critical evaluation of force fields, The sampling challenge, Grid computing methods for dynamics, What is the role of chemical detail?, Protein folding theories
Reviewed at 2020/08/12